Stratification economics and racial disparities in U.S. K−12 education - Templeton, Da'Shay; Korchagin, Ruslan (Frontiers in Education, 2025)
This manuscript introduces and applies the framework of stratification economics to understand persistent educational disparities between Black and White American K-12 students. Stratification economics challenges traditional economic theories that attribute inequality primarily to individual choices and cultural factors, instead highlighting the structural, institutional, and deliberate mechanisms perpetuating racial and socioeconomic hierarchies. Drawing from interdisciplinary literature, the paper argues that U.S. educational inequality stems from systemic resource advantages favoring White Americans, evident in disparities in school quality, enrichment access, and college admissions support. The paper identifies intergenerational resource transfers as critical drivers of educational inequality, where wealthier families can consistently provide advantages to their children, thus perpetuating a cycle of privilege. Furthermore, it explores how dominant groups maintain their privileged positions through active resistance to integrative policies, affirmative action, and curricular inclusivity. Empirical evidence demonstrates that even when Black American students acquire significant human capital, systemic discrimination still hinders their economic mobility and limits their academic opportunities, particularly within STEM fields. The manuscript also addresses stereotypes and biases affecting Black American students and their families, underscoring how individual behaviors unfairly shape perceptions of entire communities. It emphasizes the importance of racially explicit public policies that directly correspond to the theoretical assumptions of stratification economics, illustrating how each policy maps onto structural mechanisms of inequality. Ultimately, the paper calls for education stakeholders to adopt stratification economics as a framework for understanding and addressing educational disparities. It advocates for policy solutions grounded in stratification economics to dismantle entrenched racial hierarchies and ensure equitable educational outcomes.